EVALUATING THE EVALUATORS IN POSTGRADUATE FELLOWSHIP EXAMINATIONS - A VIEWPOINT - AJAO, OG (West African College of Surgeons, 2011)
When the result of a medical examination for a group of candidates is bad, it may be because the candidates are bad; or the questions and the format of the examination are improper. The reason may also be because there is no teaching and preparation of the residents or the mode of examination and the methods of assessment are flawed. This paper tries to focus attention on the role of the examiners in conducting a medical postgraduate examination. It highlights the negative impact of the aggressiveness of the evaluators, the unnecessary interruption of the candidate by the examiners and flawed or inadequate assessment of the candidate by the examiners.